pemberdayaan PEMBERDAYAAN IBU RUMAH TANGGA DALAM MENGELOLA SAMPAH RUMAH TANGGA UNTUK MENINGKATKAN PENDAPATAN KELUARGA DI RT 01 DAN RT 02 KLAPANUNGGAL - Ritonga, Rosi Feirina; Sari, Prima Mutia; Erwin, Erwin Erwin (Uhamka Press, 2019)
Rubbishs were a big problem that were faced by many people. It was also felt by the people in RT 01 and RT 02 Kelurahan Klapanunggal Kecamatan Klapanunggal. Some problems that faced by that people was less of garbage transport. It caused full of rubbishs in its place which was produced a bad smell and healthy problem. Furthermore, 70% of household wife in that place were not working. Based on these problems, the dedication activities conducted was comprehensive training that consist was training in organic waste management by making takakura compost and training in anorganic waste management by making household craft. There were four things that participants got after the training  a) Knowledge, after the training it was seen that 100% of the participants were happy and got a lot knowledge from the waste management training activities, b) Skills, based on the observations, 85%  of the participants had the skills to manage organic waste into takakura compost, c) Attitude (behavior), from the training activities develop environmental caring of participants, d) Product,), participants were able to manage their own household waste, and make it a product , like takakura fompost. The difficulties in this activity related to the allocation of time and equipment used.